Strategi Manajemen SDM Berbasis Self efficacy dan Motivasi untuk Meningkatkan Kinerja di PT Bank Rakyat Indonesia (Persero) Tbk. Cabang Denpasar - Indrayana, I Putu Dony; Sudana, I Putu Ekapratama Rangga (CV. ITTC INDONESIA, 2025)
Employee performance in the banking sector is often influenced by internal psychological factors, one of which is self-efficacy. The main issue identified is the varying levels of self-confidence among employees, which affects their motivation and work outcomes. This study aims to analyze the effect of self-efficacy on employee performance with work motivation as an intervening variable at PT Bank Rakyat Indonesia (Persero) Tbk., Denpasar Branch. This research employs a quantitative approach with a causal associative design. The population consists of 50 employees from the operational and marketing divisions, using a census sampling technique. Data were collected through questionnaires and interviews, then analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS version 4.0. The results indicate that self-efficacy has a positive and significant effect on both work motivation and employee performance. Furthermore, work motivation also has a positive and significant effect on employee performance and mediates the relationship between self-efficacy and performance. Thus, enhancing self-efficacy and work motivation plays an essential role in improving optimal performance within a competitive and digitally driven banking environment.